(untitled) (Sciences & Technology. A, exactes sciences, 2007)
We present electrochemical impedance spectra made on gold alloy containing 30% silver electrodes of various roughnesses in aqueous perchlorate acid solution as supporting electrolyte in the absence and the presence of mM of specifically adsorbed halide ions X (X = Br-, Cl-, I-), at potentials where the dominant electrode process is the adsorption of the above anions. Efforts were mainly concentrated on the importance of surface preparation technique of the electrode and its influence on impedance spectra. Atomic scale inhomogeneities are introduced by mechanical treatment and can be decreased by annealing. Due to the annealing the double layer behaves as (almost) an ideal capacitance in the absence of specific adsorption though surface roughness remains the same. A study of the related impedance behaviour in the presence of adsorbates even at very low concentrations (10-4M), revealed capacitance dispersion increasing with the extent of specific anion adsorption at the gold/silver surface.